The Normal Cross Numerical Method Used to Solve the Anisotropic Diffusion Problem - LIU Xiaogang; LIAO Jipeng; CHEN Juhui; LU Yiping; SUN Haifeng (Journal of Harbin University of Science and Technology)
In order to solve the two dimensional anisotropic diffusion problem, an efficient normal crossing numerical method was proposed. The program was written in FORTRAN language to realize numerical calculation. The method was compared with the equilibrium point method and the adaptive method. The anisotropic and anisotropic diffusion problems with analytic solutions are simulated by using a variety of rules and twisted meshes.The normal cross method decomposes the normal part into two parts: the current unit and the adjacent unit, and the diffusion cross part is displayed and processed according to the source term. It takes less time to solve the anisotropic diffusion problem than the equilibrium point method and the adaptive method, and has important application value in engineering.